Drought‐responsive genes, late embryogenesis abundant group3 (LEA3) and vicinal oxygen chelate, function in lipid accumulation in Brassica napus and Arabidopsis mainly via enhancing photosynthetic efficiency and reducing ROS. Issue 11 (26th April 2019) - Liang, Yu; Kang, Kai; Gan, Lu; Ning, Shaobo; Xiong, Jinye; Song, Shuyao; Xi, Lingzhi; Lai, Senying; Yin, Yongtai; Gu, Jianwei; Xiang, Jun; Li, Shisheng; et al.
Summary: Drought is an abiotic stress that affects plant growth, and lipids are the main economic factor in the agricultural production of oil crops. However, the molecular mechanisms of drought response function in lipid metabolism remain little known. In this study, overexpression (OE) of different copies of the drought response genes LEA3 and VOC enhanced both drought tolerance and oil content in Brassica napus and Arabidopsis . Meanwhile, seed size, membrane stability and seed weight were also improved in OE lines. In contrast, oil content and drought tolerance were decreased in the AtLEA3 mutant ( atlea3 ) and AtVOC‐RNAi of Arabidopsis and in both BnLEA‐RNAi and BnVOC‐RNAi B. napus RNAi lines. Hybrids between two lines with increased or reduced expression (LEA3‐OE with VOC‐OE, atlea3 with AtVOC‐RNAi) showed corresponding stronger trends in drought tolerance and lipid metabolism. Comparative transcriptomic analysis revealed the mechanisms of drought response gene function in lipid accumulation and drought tolerance. Gene networks involved in fatty acid (FA) synthesis and FA degradation were up‐ and down‐regulated in OE lines, respectively. Key genes in the photosynthetic system and reactive oxygen species (ROS) metabolism were up‐regulated in OE lines and down‐regulated in atlea3 and AtVOC‐RNAi lines, including LACS9, LIPASE1, PSAN, LOX2 and SOD1 . Further analysis of photosynthetic and ROS enzymatic activities confirmed that the drought response genes LEA3 and VOC altered lipid accumulation mainly via enhancing photosynthetic efficiency and reducing ROS. The present study provides a novel way to improve lipid accumulation in plants, especially in oil production crops.